2010
DOI: 10.1007/s00415-010-5619-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving gait and promoting retention in individuals with Parkinson’s disease: a pilot study

Abstract: We examined intensive walking practice using two instructional strategies on gait in Parkinson's disease (PD) before and after training and on delayed retention tests. During four training sessions (15 practice trials of walking per session), subjects (N = 6 per group) were given either verbal instruction (VI) to "take a big step" or VI plus augmented feedback (FB). For FB, videotape performance-feedback (from prior trial) supplemented by performance-cues (for subsequent trial) was given after each trial. On p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The changes in gait kinematics observed in this study suggest that individuals with mild to moderate PD are capable of cognitively using verbal instructional cueing strategies to improve gait, and that after a two-week period of active practice these PD to self-cue, a prospect that has previously been raised by Werner and Gentile (2010).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The changes in gait kinematics observed in this study suggest that individuals with mild to moderate PD are capable of cognitively using verbal instructional cueing strategies to improve gait, and that after a two-week period of active practice these PD to self-cue, a prospect that has previously been raised by Werner and Gentile (2010).…”
Section: Discussionmentioning
confidence: 60%
“…Despite the neuropathology of the disease, evidence suggests that individuals with PD are capable of improving their gait via motor learning strategies (Felix et al, 2012;Fok, Farrell, McMeeken, & Kuo, 2011;Pendt, Reuter, & Müller, 2011;Rochester et al, 2010;Werner & Gentile, 2010), as evidenced by the fact that exercise and movement strategy training have been found collectively to contribute to improvements in gait (Rochester, Nieuwboer, & Lord, 2011). For example, research focused on the nonpharmacological management of gait impairment in PD has found that the use of external cues is generally effective (Morris, Iansek, Matyas, & Summers, 1996;Rochester et al, 2010;Rochester et al, 2005;Spaulding et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have investigated various rehabilitation strategies using sensory cues for their impact on gait and falls of PD patients 4) . Studies have shown short-term improvements in parkinsonian gait when external cues are provided (visual or auditory) or when verbal instructions to increase step length are given 5) . However, few studies have investigated the effect of these factors on movement smoothness during gait performance.…”
Section: Introductionmentioning
confidence: 99%